Yizani Sifunde: The design of a multi-pronged intervention for early literacy - von Blottnitz, Magali (Liberty Community Trust, Wordworks, Book Dash and Nal'ibali, 2024)
This is the first in a series of learning briefs that explore the design, implementation and impact of Yizani Sifunde, a collaborative multi-pronged intervention designed to boost early literacy outcomes in 4- and 5-year-olds. This brief describes: • how the intervention was designed; • how close monitoring of implementation enabled improvements to the design over time.
Exploring the impact of a collaborative, multi-pronged early literacy intervention on 4- and 5-year-olds - Brief 1
Yizani Sifunde (isiXhosa for “come, let’s read”) aimed to boost early literacy outcomes at under-resourced early childhood development (ECD) centres in the Eastern Cape. It was implemented in three one-year cycles between 2021 and 2023. The project was initiated and funded by the Liberty Community Trust, and jointly designed and delivered by three literacy nonprofits: Book Dash, Nal’ibali and Wordworks. Local Eastern Cape partners ITEC and Khululeka supported implementation. More information about Yizani Sifunde is available on the Book Dash website https://bookdash.org/yizani-sifunde/
Keywords: Early learning; Early literacy; Early Childhood Development; Yizani Sifunde; South Africa; Eastern Cape; ECD centres; Liberty Community Trust; Wordworks; Nal'ibali; Book Dash; Khululeka; ITEC; Pre-Grade R; Collaboration; Triple-Cocktail approach; Children's Books; Book ownership; Little Stars; Story Sparkers; Reading